Progress in the accuracy and resolution of the Late Cretaceous Planktonic Foraminiferal Biozonation: diversification of Dicarinella and Marginotruncana and biostratigraphic implications. - M.R. Petrizzo; F. Falzoni; B. T. Huber (2013)
A recurrent feature in the evolutionary history of the planktonic foraminifera is the modification from unkeeled and globigeriniform ancestors to keeled and globorotaliform descendants. Single-keeled trochospiral taxa first appear in the Albian and correspond to a pronounced species diversification associated with an increasing degree of calcification and test size. The acquirement of peripheral double-keels is an evolutionary novelty first observed in the uppermost Cenomanian-lower Turonian assemblages. Double-keeled specimens are traditionally included in the genus Dicarinella if all the umbilical sutures are radial and depressed, whereas those forms with raised and sigmoidal to curved umbilical sutures have been included in Marginotruncana. After the extinction of the single-keeled rotaliporids close to the Cenomanian/Turonian boundary, the recovery of keeled planktonic foraminifera was relatively slow in the basal Turonian and then progressively accelerated. This diversification is well documented by the appearance of several species of Dicarinella and Marginotruncana that dominate the Turonian-Santonian assemblages. Superimposed on this evolutionary trend are occurrences of common transitional forms yielding morphological features in between Dicarinella and Marginotruncana (i.e., umbilical sutures initially raised then depressed and/or initially radial then curved, and combined patterns of the sutures), so that some of the diagnostic characters currently used to discriminate genera appear inadequate. In an effort to determine the ancestor-descendant relationships among species of Dicarinella, Marginotruncana and taxa possessing intermediate morphological features, the well preserved and highly diversified planktonic foraminiferal assemblages recovered at Tanzania Drilling Project (TDP) Sites 31 and 39 (coastal Tanzania; see Jiménez Berrocoso et al., 2012) and at Ocean Drilling Program (ODP) Sites 762 and 763 (Exmouth Plateau; see Petrizzo et al., 2011) have been studied. The morphological features ...